Modifications of OSCE for UPM preclinical medical students during COVID-19 pandemic - Mahayidin, Hasni; Adam, Siti Khadijah; Hassan, Haniza; Salihan, Safuraa (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
The social and physical restrictions in the early phase of COVID-19 pandemic had resulted in forced transition into virtual learning worldwide. Modifications of assessment tools also had to be made to suit online conduct. This article aims to share the experience of conducting online objective structured clinical examination (OSCE) using several approaches for preclinical medical students in one of the public universities in Malaysia. It summarises the challenges faced by the involved parties, as well as the solution and recommendation should similar situation arises in the future.